Risiko gizi lebih pada anak usia prasekolah berdasarkan aspek sosio-ekonomi keluarga di Kota Kediri - Nining Tyas Triatmaja (AcTion: Aceh Nutrition Journal, 2022)
Overweight in children under five has increased and will impact at an early age and cause a metabolic syndrome in adulthood. Being overweight is caused by many things, one of which is socioeconomic family. Family socioeconomic is an underlying cause that influences feeding practices. This study aimed to analyze the risk of overweight in preschool children based on family socio-economics. This study used a case-control design conducted from December 2019 to March 2020. The sample used was 66 preschool children divided into two groups with a ratio of 1:1, which was carried out by simple random sampling—data collection techniques by interviewing sample mothers related to the socioeconomic aspects of the family. Data were processed using SPSS software and categorized each variable into two categories. Data analysis using Chi-Square test. The results of this study showed: that maternal nutritional knowledge was significantly correlated with the incidence of overweight in preschool children (p= 0,041). Other socio-economic aspects (maternal age (p= 0,202), paternal age (p= 0,250), maternal education (p= 0,450), paternal education (p= 0,301), family size (p= 0,439), and family economic status (p= 0,395) were not correlated with the overweight. This study concluded that maternal nutritional knowledge was one of the factors associated with overweight in preschool children, while other socioeconomic factors were not related.